The Ethnic Rohingya Identity Crisis In Myanmar: Politicization Of Identity And Implications On Human Rights - Sinaga, Kezia Marlinata; Charren Galuh Indaswari; Princess Ngozi Chika; Ummah, Aniqotul (ARRUS Journal of Social Sciences and Humanities, 2024)
This research examines the identity crisis experienced by the Rohingya Ethnic group in Myanmar and how the politicization of identity impacts human rights violations against this minority group. The Main focus of the research is to analyze the politicization process of Rohingya ethnic identity conducted by the Myanmar government through discriminatory policies, as well as to identify its implications for the fulfillment of basic human rights. Using a qualitative approach with literature study methods, this research finds that the Rohingya ethnic identity crisis stems from the Myanmar government's systematic refusal to recognize their existence as an official ethnic group. Identity politicization is reflected through the implementation of the 1982 citizenship law that revokes Rohingya citizenship, restrictions on access to education, health, and employment, as well as acts of violence resulting in mass displacement. The implications of this identity politicization include severe human rights violations such as murder, torture, rape, and village burning that have forced hundred of thousands of Rohingya to seek refuge in neighboring countries. This research concludes that the identity crisis and politicization experienced by the Rohingya ethnic group has created a cycle of violence and ongoing human rights violations that requires serious attention and handling from the international community Keywords : Rohingya, Myanmar, Identity Crisis, Identity Politicization, Human Rights.